Challenges to HIV treatment adherence amongst adolescents in a low socio-economic setting in Cape Town - Brian E. van Wyk; Lee-Ann C. Davids (AOSIS, 2019)
Background: Despite the successful rollout of anti-retroviral therapy (ART) and steep declines in HIV incidence in South Africa, this has not been the case for adolescents (10-19 years). Adolescents on HIV treatment have lower rates of viral load suppression and adherence compared to adults and children. Objectives: This article reports on the adherence challenges faced by adolescents receiving ART in a primary health care clinic in a low socio-economic urban setting in Cape Town. Method: An exploratory qualitative design was employed where data were collected through four focus group discussions with adolescents (n = 15) who received ART at a primary health care clinic in a low socio-economic urban setting in Cape Town and followed up with eight individual, semi-structured interviews with two adolescents from each focus group. Two key informant interviews were conducted with health workers at the clinic. Audio data were digitally recorded and transcribed verbatim. Data were analysed using content analysis. Results: School commitments, strained teacher-learner relationships, negative household dynamics and ill treatment by non-biological caregivers were reported as major barriers to adherence. In addition, poor service delivery, missing or misplaced files and long waiting times came under major criticism. Fear of unintended disclosure of HIV status, stigma and discrimination, treatment fatigue and having unstructured lives negatively influenced adherence. Having a strong social support system and having life goals and ambitions were motivators to remain adherent. Conclusion: This study highlighted the complexity of ART adherence in the midst of juggling school, home life and personal life goals and aspirations. Interventions to improve adherence should address psychosocial factors such as treatment fatigue, disclosure and family and household dynamics, in addition to streamlining service delivery between the school and clinic.